Thailand-Malaysia border: a strategic route for illicit drug trade from the golden triangle - Dunita Nabila A. Rahimin; Wong, Danny Tze Ken (Penerbit Universiti Kebangsaan Malaysia, 2025)
Nestled between Burma (Myanmar), Thailand, and Laos, the Golden Triangle has long been a critical nexus for illicit drug production and trafficking, establishing itself as one of the world’s most notorious hubs for the global drug trade. The region’s geographical location, coupled with its porous borders, has made it an ideal centre for the cultivation and trafficking of opium, heroin, and other illicit substances. The proximity of Malaysia to Thailand, in particular, has made the Thailand-Malaysia border a significant transit route for smuggling drugs from the Golden Triangle into Malaysia. This study delves into the drug trafficking operations originating from this region, with particular emphasis on the 1970s and 1980s, when the flow of illicit substances into Malaysia surged. During this period, Malaysia faced increasing challenges due to the influx of drugs, prompting the government to take decisive action. Using a qualitative methodology by analysing archival documents from Arkib Negara Malaysia and Central Intelligence Agency (CIA) reports, this research highlights how Malaysia responded to the escalating drug trade. The study traces the evolution of Malaysia’s drug control policies, culminating in the country’s aggressive stance in the 1980s. In 1983, the government declared a "war on drugs," introducing harsh penalties and intensifying law enforcement efforts. Moreover, the study underscores the importance of cross-border cooperation in tackling the drug trade. The Thailand-Malaysia border, heavily impacted by Golden Triangle trafficking, led to increased collaboration between the two nations’ intelligence agencies. Malaysia also worked closely with ASEAN to bolster regional efforts aimed at curbing the spread of drug trade across Southeast Asia. The study concludes that these multi-pronged responses were essential in combating the growing threat posed by the Golden Triangle’s drug trade in the latter half of the 20th century.